Implementasi Kansei Engineering pada Aplikasi E-learning Untuk Sekolah Menengah Kejuruan - Megasyah, Yoga (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
E-learning is the basis and logical consequence of the development of information and communication technology. With E-learning, teaching and learning methods in schools that use technology through electronic media such as computers, laptops, netbooks, or smartphones with internet networks or others. This study uses Kansei Word to detect the feelings of users of E-learning applications. The Kansei Word list is used as many 15 words related to the appearance of the E-learning application. E-learning application specimens used 8 specimens. This study involved 80 participants consisting of 40 students from SMK PGRI 3 Cimahi, 40 students from SMK 4 Padalarang. The questionnaire results from participants were then processed using multivariate statistical analysis, namely Cronbach's Alpha, Coefficient Correlation Analysis (CCA), Principal Component Analysis (PCA), Factor Analysis (FA) and Partial Least Square (PLS) analysis. This study produced 3 recommendations for the design of E-learning application. This recommendation is the result of the Kansei Engineering process which comes from 3 groups of participant data, namely groups of data of all participants, participants of SMK PGRI 3 Cimahi students and participants of SMK 4 Padalarang students.